Patogenisitas jamur entomopatogen beauveria bassiana terhadap walang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The objective of this research was to determine the pathogenicity of the entomopathogenic fungi Beauveria bassiana to the rice bug (Leptocorisa oratorius F.). An isolate was obtained from the infected rice bugs in the regency of Bantul. The starter of rice bugs were collected from field and reared in the green house. The rice bugs were released in to the rice plants in the cages. Bioassay were carried out by spraying the rice plants (3.2 ml/ hill) with the concentration of B. bassiana ranging from 3.2 x 102 to 3.2 x 1011 conidia/ml. The LC50 value of B. bassiana against the adults was 3.8 x 108 conidia/mI for one week exposure. The first instar was found to be more receptible than those of the third instars and adults. To reach 60% mortality for these stadia, it took the concentrations of B. bassiana as much as 3.8 x 108, 3.8 x 109, and 3.8 x 1010 conidia/ Ind, respectively. The nymphs survived from the applications of B. bassiana caused less damage on the rice seeds than the control.